Synergizing IoT and digital twin technology for revitalizing the ready made garments industry’s supply chain through simulation and modeling - Mridha, Mohammad Tuhin (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2024.